Handbook for defining and setting up a Food Security Information and Early Warning System (FSIEWS) (FAO RomeIT, 2001)
The aim of this handbook is to give a description of the FSIEWS method for the benefit of the community of governmental and non-governmental actors engaged in the fight against hunger.
Keywords: FAO